2018
DOI: 10.1021/acscatal.8b02184
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of the Hemiaminal Intermediate in the Iron-Catalyzed Deaminative Hydrogenation of Amides

Abstract: The source of hydrogen atoms will determine the reaction hazard, cost, and reaction conditions. Hydrogen sources can be classified into two main groups: hydride or molecular hydrogen sources. [3][4][5][6]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 115 publications
2
25
0
Order By: Relevance
“… 48 This is in agreement with previous DFT calculations from the same group, highlighting the TOF-limiting nature of this step that is facilitated by the employed iron complex or via proton relay by a solvent/reactant molecule. 49 We were thus interested how these observations translate to our system. Again, the test amide seems not to be acidic enough to serve as an efficient proton relay for the generation of the labile zwitterion ( TS3D1 , 43.1 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
“… 48 This is in agreement with previous DFT calculations from the same group, highlighting the TOF-limiting nature of this step that is facilitated by the employed iron complex or via proton relay by a solvent/reactant molecule. 49 We were thus interested how these observations translate to our system. Again, the test amide seems not to be acidic enough to serve as an efficient proton relay for the generation of the labile zwitterion ( TS3D1 , 43.1 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
“…For case of brevity, the focus will be on processes involving carbon dioxide and dinitrogen as the main substrates of interests, as well as chemical transformations promoting the valorization of biomass-derived molecules. Nevertheless, pincer complexes have achieved remarkable results in the (transfer) hydrogenation of a wide series of substrates such as ketones [385,[457][458][459][460][461][462], esters [40,179,220,386,400,[463][464][465][466][467][468][469][470][471][472][473][474][475][476][477], aldehydes [478][479][480], amides [67,[481][482][483][484][485], and imines [486,487]. After screening a range of amines, Prakash and Olah demonstrated the same concept using Ru-MACHO-BH and dimethylethylenediamine (5.3 wt% H2) which was successfully dehydrogenated in the presence of methanol resulting in a mixture of formamides [455].…”
Section: Hydrogenation Reactionsmentioning
confidence: 99%
“…The hydrogenation of formanilide, morpholidine and dimethylformamide (DMF) by an iron Noyori-type catalyst was studied by our group in 2018 (see Fig. 6) [24,27]. In this study, it was found that all transition states were thermally accessible, and that the formation of most intermediates and products was endergonic.…”
Section: Reaction Mechanisms For Amide C=o Hydrogenationmentioning
confidence: 99%
“…Examples of reaction mechanisms for the C=O hydrogenation of different amides with bifunctional Noyori-type catalysts [24,26,27,34]. R = CO for M = Mo and Mn.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation